2022
DOI: 10.3390/buildings12081203
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Embodied Carbon and Strategies for Decarbonization of a High-Rise Residential Building

Abstract: The construction sector is responsible for the 40% of consumed resources, 40% of CO2 emissions, and approximately 40% of construction and demolition waste. For the assessment of the building, there exists a standardized method, life cycle assessment (LCA), however, the process requires time, cost, and most importantly expertise. In this paper, a method is proposed and analyzed for the life cycle assessment of the building for the embodied carbon in the three stages, construction, operation, and demolition. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The theoretical approach is tested and validated against experimental measurements conducted during the winter months. The validated theoretical approach is then employed to predict the system performance for the variation in following parameters: air gap width variations (2, 4, 6, and 10 cm), massive wall thickness ranging from 15 to 35 cm with 5 cm increments, channel width options (3,5,10,15, and 20 cm), and vent heights ranging from 5 to 20 cm in 5 cm increments. In addition, an investigation into the effect of replacing the air in the air gap with inert gases, specifically argon, krypton, and a mixture of these gases with air has been carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical approach is tested and validated against experimental measurements conducted during the winter months. The validated theoretical approach is then employed to predict the system performance for the variation in following parameters: air gap width variations (2, 4, 6, and 10 cm), massive wall thickness ranging from 15 to 35 cm with 5 cm increments, channel width options (3,5,10,15, and 20 cm), and vent heights ranging from 5 to 20 cm in 5 cm increments. In addition, an investigation into the effect of replacing the air in the air gap with inert gases, specifically argon, krypton, and a mixture of these gases with air has been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the building industry carries a significant portion of the responsibility, accounting for around 40% of worldwide energy consumption and 36% of carbon dioxide emissions. 2,3 To overcome these issues, one of the essential solutions is adoption of renewable energy sources. Renewable energy is now one of the most promising technologies for powering and heating buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Alotaibi, Badr Saad, et al [16] conducted a study focused on high-rise residential buildings, examining embodied carbon emissions and decarbonization strategies. Their research introduced and evaluated a LCA method covering construction, operation, and demolition phases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the fact that in energy-efficient buildings, embodied carbon can contribute up to 80% of lifetime GHG emissions [8], several studies [9,10] including by Liang et al (2019) have suggested focusing more on examining the ratio between embodied and operational carbon to fully explore the decarbonisation potential of an entire building's life cycle [5].…”
Section: Introductionmentioning
confidence: 99%